Oblomov - Goncharov, Ivan Aleksandrovich, 1812-1891; Hogarth, C. J. (Charles James), 1869-1942 (Salt Lake City, UT : Project Gutenberg, 2017)
"Oblomov" by Ivan Aleksandrovich Goncharov is a novel published in 1859. It follows Ilya Ilyich Oblomov, a young Russian nobleman who has perfected the art of inertia. Unable to leave his bed or make decisions, he watches life pass from his bedroom while others manage his crumbling estate. When a friend introduces him to love, Oblomov faces a choice: embrace action and purpose, or surrender to the comfortable paralysis that defines him. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Oblomov
Release date is 2017-05-10
David Widger
Keywords: Russia -- Social life and customs -- 1533-1917 -- Fiction